Studies on large deformation behavior of geometrical metallic frusta by finite element simulation - Sahu, Ram Ranjan; Gupta, Pramod Kumar (Journal of Structural Engineering, 2024)
The loading response of shell structure associated with large deformation is quite complex. While undergoing large deformation, these shell structure absorb energy. This makes shell structure a good choice for application in energy absorbing devices. These shell structure could be of many forms like frusta, tube, domes, honeycomb structures etc. A large deformation study was planned theoretically, on metallic capped end frusta with different geometrical section. The large deformation was obtained by crushing frusta between two flat plates. Finite Element analysis (FEA) was used to simulate the crush phenomenon. Frusta behavior to large deformation was understood with load displacement graph. The energy absorbed by each sample is calculated and compared. The parameters like weight, material and thickness were varied for samples to see their effect on large deformation behavior. Also friction role is discussed on crush phenomenon. This paper also gives an idea on frusta geometry, which can give good energy absorbing capacity.